2011
DOI: 10.1108/02632771111120556
|View full text |Cite
|
Sign up to set email alerts
|

Integrating sustainability and buildability requirements in building envelopes

Abstract: Purpose -The purpose of this study is to present the importance of integrating common features between the Green Mark Scheme (GMS) and the Buildable Design Appraisal System (BDAS) requirements in building envelopes. Design/methodology/approach -The study presents the common features that influence both the GM score of the building envelope and the buildability score of the wall system. A case study is developed to show the effects of varying the value of a representative common feature in the GM score and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…This can be seen for example in Singapore where there are a number of regulations implemented to promote sustainability and buildability in building designs [40]. However, compliance with these regulations does not guarantee satisfactions of the stakeholders of a building project [5]. Singhaputtangkul et al [40] suggested major criteria applied by the architects and engineers in Singapore for achieving sustainability and buildability in the assessment of the building envelope materials and designs as shown in Table 1.…”
Section: Km-cmentioning
confidence: 98%
See 3 more Smart Citations
“…This can be seen for example in Singapore where there are a number of regulations implemented to promote sustainability and buildability in building designs [40]. However, compliance with these regulations does not guarantee satisfactions of the stakeholders of a building project [5]. Singhaputtangkul et al [40] suggested major criteria applied by the architects and engineers in Singapore for achieving sustainability and buildability in the assessment of the building envelope materials and designs as shown in Table 1.…”
Section: Km-cmentioning
confidence: 98%
“…For instance, because of inadequate consideration of requirements, designers may not be able to develop a comprehensive design, which may lead to numerous adverse impacts during different project phases [16]. Singhaputtangkul et al [5] suggested that inadequate consideration of building envelope requirements by designers tends to lead to redesigning activities, particularly when new assessment criteria have to be additionally considered. These activities can cause progress delay, project delay, increase in expenses and increase in manpower needed of a building project [10].…”
Section: Inadequate Consideration Of Requirementsmentioning
confidence: 99%
See 2 more Smart Citations
“…A case study to identify the relationship between Singapore's Green Mark Scheme (GMS) and the Buildable Design and Appraisal System (BDAS)'s requirements for building envelopes was conducted by Singhaputtangkul et al [24]. Singhaputtangkul et al [24] discovered that the lengths of windows and walls and the associated materials influence the Green Mark (GM) score of the building envelope and the buildability score of the wall system. In addition, they further concluded that varying the window-to-wall (WWR) ratio has a stronger effect on the GM score, in terms of the building envelope in comparison with the buildability score of the wall system.…”
mentioning
confidence: 99%